2018
DOI: 10.1186/s13293-018-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in lower urinary tract biology and physiology

Abstract: Females and males differ significantly in gross anatomy and physiology of the lower urinary tract, and these differences are commonly discussed in the medical and scientific literature. However, less attention is dedicated to investigating the varied development, function, and biology between females and males on a cellular level. Recognizing that cell biology is not uniform, especially in the lower urinary tract of females and males, is crucial for providing context and relevance for diverse fields of biomedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 117 publications
3
46
1
1
Order By: Relevance
“…Age distribution of the patient demographics (Table 1) showed that a majority of samples (69.7%) were obtained from older patients (51 years and older). Our data is in agreement with what is previously known about the etiology of UTI's, wherein females (due to their anatomy and physiology) are more predisposed to contracting an UTI as compared to males [10]. In addition, it has been demonstrated in a number of studies, that UTI instances increase with age [11].…”
Section: Resultssupporting
confidence: 92%
“…Age distribution of the patient demographics (Table 1) showed that a majority of samples (69.7%) were obtained from older patients (51 years and older). Our data is in agreement with what is previously known about the etiology of UTI's, wherein females (due to their anatomy and physiology) are more predisposed to contracting an UTI as compared to males [10]. In addition, it has been demonstrated in a number of studies, that UTI instances increase with age [11].…”
Section: Resultssupporting
confidence: 92%
“…25 Physiologic factors that increase the probability of UTI are the hormonal factors, reticuloendothelial system and the microbiome of the lower urinary tract (LUT). 26 Mean age of the patient in this study was 57.21 years with most of the patients (47.05%) being in the age group of 18 to 40 years. Although the prevalence of bacteriuria has a higher frequency among the very young and a gradual increase with age, 27 symptomatic infection has the highest frequency among women aged 15-29 years.…”
Section: Discussionmentioning
confidence: 70%
“…More importantly, the later female dominance may be due to anatomical differences where the proximity of the urethral opening to the vagina may facilitate urethral contamination [58]. In addition, recent evidence suggests that the sex differences in the reticuloendothelial system which provides innate immunity against microbes may also contribute to the sex differences in UTI prevalence rates [59]. Thus, irrespective of nutritional status, female sex remains a risk factor for UTI in childhood.…”
Section: Discussionmentioning
confidence: 99%